ANALISA NILAI TAMBAH PENJUALAN JAMUR TIRAM SEGAR DAN KRIPIK JAMUR TIRAM DI DESA BUMIRAHAYU KECAMATAN BUAY MADANG TIMUR KABUPATEN OKU TIMUR - Ary Eko Prastya Putra (Jurnal Bakti Agribisnis, 2018)
The objectives of this study were to: 1) determine the business income of selling fresh oyster mushrooms and making oyster mushroom chips in Bumirahayu Village, Buay Madang Timur District, East OKU Regency, 2) to determine the added value of selling fresh oyster mushrooms into oyster mushroom chips in Bumirahayu Village District Buay Madang Timur, East OKU Regency. The results showed that the income earned by the oyster mushroom cultivation business actors was Rp. 10,953,697, - / PP (Rp. 2,738,424, - / month). Meanwhile, the business of making oyster mushroom chips is Rp. 988. 437, - / PP (Rp. 3,953,748, - / month). The difference in income that is quite large makes the business of making oyster mushroom chips feasible to be developed, while the added value in the business of making oyster mushroom chips is Rp. 12,437, - / Kg or in the amount of Rp. 1,305,937, - / PP (Rp. 5,223,748, - / month) obtained from the difference between the final value and the cost of raw materials.